ANALYSIS OF MECHANICAL PROPERTIES OF PARTICLE BOARD BASED DURIAN SKIN AND SUGAR CANE BAGASSE WITH FORMALDEHIDA UREA ADHESIVE - Ety Jumiati; Rika Safitri; Abdul Halim Daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
The particle board was made based on mixing durian skin and sugar cane bagasse with urea formaldehyde adhesive. The variations the composition of mixing durian skin, sugar cane bagasse with urea formaldehyde adhesive used among other: 35%:35%:30%, 30%:30%:40%, and 25%:25%:50% and printing time and pressing for 24 hours. The parameters of the testing include: Modulus of Rupture (MOR) dan Modulus of Elasticity (MOE). Analysis of the mechanical properties of the particle board produced at the composition of 35%:35%:30% which has a value MOR = 446,17 kgf/cm2 and MOE = 160,9 kgf/cm2, at the composition of 30%:30%:40%, has a value MOR = 1369,57 kgf/cm2 dan MOE = 3903,3 kgf/cm2, at the composition of 25%:25%:50%, has a value MOR = 1463,07 kgf/cm2,  dan MOE = 3342,1 kgf/cm2 which matches SNI 03-2105-2006 criteria type 8 is not required.